Residents' perceptions towards educational tourism impacts: the role of gender differences - Ahmadian, Maryam; Abu Samah, Asnarulkhadi; Gill, Sarjit S.; Saidu, Mohammed Bashir; Hendijani, Roozbeh Babolian (Canadian Center of Science and Education, 2014)
Urban residents were surveyed to identify their perceptions, attitudes and practices about educational tourism in Malaysia. The purpose of this paper was also to assess if there were gender differences in host communities towards educational tourism impacts. Descriptive and inferential statistical analysis was performed; the results demonstrated that there was a significant difference in gender on educational tourism impacts (p < .05). The findings suggest that further qualitative studies should be done in order to value social and cultural factors concerning host communities, gender differences and tourism industry in Malaysia. The study could contribute to educational tourism policy, community development and sustainability in future programs.